A new biocatalyst: Penicillin G acylase immobilized in sol‐gel micro‐particles with magnetic properties - Bernardino, Susana M. S. A. (2009)
The present work focuses on the development and basic characterization of a new magnetic biocatalyst, namely penicillin G acylase (PGA), immobilized in sol-gel matrices with magnetic properties, ultimately aimed for application in cephalexin (CEX) synthesis. A mechanically stable carrier, based on porous xerogels silica matrixes starting from tetramethoxysilane (TMOS), was prepared leading to micro-carriers with medium sized particles of 30 μm, as determined by scanning electron microscopy. An immobilization yield of 95-100% and a recovered activity of 50-65% at 37°C, as determined by penicillin G (PG) hydrolysis (pH STAT method), were observed. These results clearly exceed those reported in a previous work on PGA immobilization in sol-gel, where only 10% of activity was recovered. The values of activity were kept constant for 6 months. Immobilized PGA (682 U/gdry weight) retained high specific activity throughout ten consecutive runs for PG hydrolysis, suggesting adequate biocatalyst stability. The CEX synthesis was performed at 14°C, using the free and immobilized PGA in aqueous medium. Phenylglycine methyl ester was used as acyl donor at 90 mM and 7-aminodeacetoxycephalosporanic acid was the limiting substrate at 30 mM. The CEX stoichiometric yield after 1-h reaction was close to 68% (23 mM CEX/h) and 65% (19 mM CEX/h), respectively.